An Updated Multi-Temporal Glacier Inventory for the Patagonian Andes With Changes Between the Little Ice Age and 2016 - Meier, Wolfgang J.-H.; Grießinger, Jussi; Hochreuther, Philipp; Braun, Matthias H. (Frontiers in Earth Science, 2018)
We present a satellite-derived glacier inventory for the whole Patagonian Andes south of 45.5°S and Tierra del Fuego including recent changes. Landsat TM/ETM+ and OLI satellite scenes were used to detect changes in the glacierized area between 1986, 2005 and 2016 for all of the 11.209 inventoried glaciers using a semi-automated procedure. Additionally we used geomorphological evidence, such as moraines and trimlines to determine the glacierized area during the Little Ice Age for almost 90% of the total glacierized area. Within the last ~150 years the glacierized area was reduced from 28.091±890 km2 to 22.636±905 km2, marking an absolute area loss of 5.455±1.269 km2 (19.4%). For the whole study region, the annual area decrease was moderate until 1986 with 0.10±0.04% a-1. Afterwards the area reduction increased, reaching annual values of 0.33±0.28% a-1and 0.25±0.5% a-1 for the periods of 1986-2005 and 2005-2016, respectively. There is a high variability of change rates throughout the Patagonian Andes. Small glaciers, especially in the north of the Northern Patagonian Icefield (NPI) and between the latter and the Southern Patagonian Icefield (SPI) had over all periods the highest rates of shrinkage, exceeding 0.92±1.22% a-1 during 2005-2016. In the mountain range of the Cordillera Darwin (CD), and also accounting for small ice fields south of 52°S, highest rates of shrinkage occurred during 1986-2005, reaching values up to 5.6±4.2% a-1, but decreased during the 2005-2016 period. Across the Andean main crest, the eastern parts of the NPI, SPI and adjoined glaciers had in absolute values the highest area reduction exceeding 2.145±482 km2 since the LIA. Large calving glaciers show a smaller relative decrease rate compared to land-terminating glaciers but account for the most absolute area loss. In general, glacier shrinkage is dependent on latitude, the initial glacier area, the environment of the glacial tongue (calving or non-calving glaciers) and in parts by glacial aspect.